2016
DOI: 10.1111/jam.13027
|View full text |Cite
|
Sign up to set email alerts
|

Farnesol increases the susceptibility of Burkholderia pseudomallei biofilm to antimicrobials used to treat melioidosis

Abstract: The intrinsic antimicrobial resistance of B. pseudomallei is a serious challenge for the treatment of melioidosis. Thus, this paper reports the inhibitory potential of farnesol against B. pseudomallei biofilms, as well as highlights the favourable pharmacological interaction of farnesol with antibiotics tested, not only on cell viability, but also in the structural morphology of biofilms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The COMSTAT analyses were used for quantitative analysis of the image stacks produced by CLSM (Heydorn et al 2000). The evaluated parameters obtained for the live biofilm cells included biofilm average coverage, average thickness, and biovolume, whereas thresholding was automatically calculated as previously described (Castelo-Branco et al 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The COMSTAT analyses were used for quantitative analysis of the image stacks produced by CLSM (Heydorn et al 2000). The evaluated parameters obtained for the live biofilm cells included biofilm average coverage, average thickness, and biovolume, whereas thresholding was automatically calculated as previously described (Castelo-Branco et al 2016).…”
Section: Methodsmentioning
confidence: 99%
“…A recent study conducted by Castelo-Branco et al [75] showed potentiation effects of a combination therapy of farnesol with amoxicillin, doxycycline, ceftazidime, and sulfamethoxazole-trimethoprim against B. pseudomallei . A phenol sesquiterpene, xanthorrhizol was found to reduce 60% of Staphylococcus mutans cell adherence ability [76], and inhibited the growth of Mycobacterium smegmatis [77].…”
Section: Terpenes and Their Derivativesmentioning
confidence: 99%
“…Castelo-Branco et al (2012) showed a potent antimicrobial effect exerted by exogenous farnesol exposure against mature Burkholderia pseudomallei biofilms [ 90 ]. Additionally, it increased the activity of amoxicillin, ceftazidime, doxycycline, and sulfamethoxazole-trimethoprim, which are routinely administered for the treatment of melioidoses [ 91 ]. Farnesol also had a synergizing effect against ciprofloxacin-resistant Pseudomonas aeruginosa biofilms when used in combination with ciprofloxacin [ 92 ].…”
Section: Farnesolmentioning
confidence: 99%